Heat stress: A growing crisis for women farmers - Kori, Pooja; Verma, Benu; Puskur, Ranjitha (International Rice Research Institute, 2025)
This booklet was designed to disseminate learnings from the project on 'Heat Stress, Agriculture and Gender’, conducted in Ganjam, Mayurbhanj and Balangir districts of Odisha, India funded by the CGIAR GENDER Impact Platform. The project, through qualitative assessments and training workshops, unpacked the impact of heat stress on the lives and livelihoods of women farmers, the measures they take to tackle it and the enabling policy environment.